Some fishing and biological aspets of crocodile shark Pseudocarcharias kamoharai (Matsubara, 1936) in tuna longline in Indian Ocean - Prawira A. R. P. Tampubolon; Dian Novianto; Abram Barata (Jurnal Iktiologi Indonesia, 2016)
Crocodile shark, Pseudocarcharias kamoharai (Matsubara 1936) is one of the non-target species which is caught by tuna longlines. This shark is the discards fish in tuna longline fisheries and only their liver are utilized. The aims of this research were to determine some aspects relating to the fishing (fishing areas and hook rate) and biological aspect (size distribution and sex ratio) of the crocodile shark. The data were collected directly via observation in tuna longline commercial fishing vessels based in Palabuhanratu, Cilacap and Benoa. The observations were carried out from February 2012 to October 2014 in Indian Ocean. The crocodile sharks were caught at 6o44'42" S to 32o59'49" S latitude and 85o34'34" E to 120o20'35" E longitude. The hook rate of crocodile shark was fluctuated and the average in 20122014 was 0.39. A total of 288 crocodile sharks were caught during the study period. However, only 182 of them could be measured. The size of male crocodile sharks were between 54-112 cm long; while the female fish were 51-117 cm. Sex ratio of crocodile shark was balance. Abstrak Hiu buaya, Pseudocarcharias kamoharai (Matsubara, 1936) merupakan salah satu spesies non target yang turut tertang-kap di rawai tuna. Ikan ini merupakan ikan buangan yang umumnya hanya diambil hatinya saja. Tulisan ini bertujuan untuk menentukan beberapa aspek yang bertalian dengan aspek penangkapan ikan hiu buaya seperti daerah tertangkap dan laju pancing serta sebaran ukuran dan nisbah kelamin. Data dikumpulkan dengan melakukan pengamatan langsung pada kapal penangkap ikan komersial yang menggunakan alat tangkap rawai tuna. Pengamatan dilakukan mulai Februa-ri 2012 hingga Oktober 2014. Kapal komersial ini beroperasi di Samudra Hindia dan berbasis di Palabuhanratu, Cila-cap, serta Benoa. Hiu buaya yang tertangkap menyebar pada posisi 6°44’42”-32°59’49” LS dan 85°34’34”-120°20’35” BT. Laju pancing hiu buaya berfluktuasi dengan nilai rata-rata sebesar 0,39 dalam kurun waktu 2012-2014. Hiu buaya yang tertangkap selama penelitian berjumlah 288 ekor. Namun, hanya 182 ekor yang dapat diukur panjangnya. Hiu buaya jantan memiliki kisaran panjang 54-112 cm; sedangkan ikan betina berukuran antara 51-117 cm. Nisbah kelamin total hiu buaya seimbang.